Conservation Implications of Genetic Differentiation in Southern African Populations of Black Rhinoceros ( Diceros bicornis ) - M. K. J. Swart; J. W. H. Ferguson (Conservation Biology, 1997)
We analyzed 30 protein‐coding loci of four southern African black rhinoceros populations in order to calculate fixation indices and genetic distances for the different populations. We concluded that one of these populations is of the subspecies Diceros bicornis bicornis and the other three of Diceros bicornis minor. No evidence of inbreeding within populations was found. F‐ statistics revealed significant differentiation between populations. Small genetic distances found among the four populations reveal that they are conspecific, and no evidence was found to support the claim that the populations belong to discrete subspecies. Rather, an east‐west cline in genetic characteristics appears to exist with G6pd and HB‐2 alleles peculiar to western populations and Es‐2 and GP‐3 alleles peculiar to eastern populations.